SYNTHESIS, CHARACTERIZATION, ANTI BACTERIAL ACTIVITY AND ECOTOXICITY OF SILVER NANOPARTICLES FROM CALLUS EXTRACT OF JUSTICIA JENDARACIA (BURM.F) - S.KARTHICK RAJA NAMASIVAYAM; Koilpillai, Y.Justine; Bharani, R.S.Arvind; K.Samrat (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective. Synthesis of silver nanoparticles from callus extract of Justicia jendaracia (Burm.f) and the anti bacterial activity ,ecotoxicity of the synthesized particles has been studied in the present study. Methods.The callus was induced in Murashige and Skoog (MS) medium supplemented with growth regulators and evaluated for nanoparticles synthesis. Anti bacterial activity was studied against human pathogenic bacteria Escherichia coli (ATCC 25922) and Staphylococcus aureus (ATCC 29213) was done by well diffusion assay.Ecotoxicity study was studied against Vigna mungo under pot assay. Results.The extract from the callus showed ability of synthesis of nanoparticles Â with plasmon absorption maxima at 430 nm, spherical particles with the size range of 50â€“65 nm. The antibacterial activity with these synthesized nanoparticles showed distinct effect on the all the tested strains. Ecotoxicity study reveals that nanoparticles did not cause any distinct effectÂ on soil macronutrients, soil enzyme activity, soil microbial population and Â plant growth parameters of Vigna mungo . Conclusion. Present study would suggest possible utilization of biogenic silver nanoparticles from theÂ callus extract of Justicia jendaracia as the therapeutic agent without causing any undesirable effects to the environment. KEY WORDS. Callus, Justicia Jendaracia, Silver Nanoparticles,Anti Bacterial Activity,Eco Toxicity